Reliability analysis for multi-state systems under K-mixed redundancy strategy considering switching failure. (December 2022) - Liu, Baoliang; Wen, Yanqing; Qiu, Qingan; Shi, Haiyan; Chen, Jianhui
Highlights: A novel multi-state K-mixed redundancy strategy reliability model is constructed. The repairman's multiple policy is adopted in the system. The versatility of the pH distributions enhances the flexibility and practicality of the systems. The performance measures of the proposed reliability model are obtained in transient and static regimes, respectively. We compare the system models with mixed redundancy strategy system model in system reliability measures and profits. Abstract: In this paper, a three components repairable system under K-mixed redundancy strategy with unreliable switching failure is proposed, in which the lifetimes of components, the repair time of failure components and the vacation time are distributed with different phase-type (PH) distributions. The multiple vacation policy of the repairman is adopted so that the human resources can be fully utilized. The proposed repairable system model is studied in both transient and stationary regimes with matrix-analytic method. Some reliability indexes are obtained by employing Kronecker operator theory and aggregated stochastic theory. Finally, a numerical example and a comparison analysis between K-mixed redundancy strategy model and mixed redundancy strategy model are implemented to illustrate the results obtained in the paper.